Bridging the gap: Enhancing Kenya's food policy with science-based evidence - Keenan, Michael; Njoroge, Grace; Breisinger, Clemens; Karugia, Joseph; Kirui, Leonard; Maru, Joyce (CGIAR System Organization, 2024)
In an era where data is more valuable than oil, the pressing need to harness scientific insights for informed policy-making, particularly in the agricultural sector, has never been more critical. Kenya, faces the challenge of feeding a growing population amidst cases of limited land, climate change, and market volatility. The recent spikes in food, fertilizer, and fuel prices have not only underscored the fragility of its food systems but also highlighted the urgency for evidence-based solutions to ensure food security, nutrition and health. This reality underscores the importance of bridging the gap between agricultural policy and science, a task that calls for a deep dive into the current state of the Science-Policy Interface (SPI) within the country. Our narrative sheds light on this crucial junction of policy and science in Kenya, exploring the multifaceted landscape where research meets policy-making. Despite the vibrant network of national and international research institutions within the country, a disconnect persists in effectively translating scientific findings into actionable policies. This disconnect not only hampers the realization of evidence-based policymaking but also constrains Kenya’s ability to institute effective food policies.